Madrasah And Pesantren Integration Curriculum Management In MAN 2 Pasuruan - Marhumah; Abu Darim (Journal of Social Science and Economics, 2023)
The purposes of this study are, the first, to describe the integrative curriculum planning of madrasah and pesantren in MAN 2 Pasuruan. Secondly, to describe the implementation of an integrative curriculum of madrasah and pesantren in MAN 2 Pasuruan, and thirdly, to describe an integrative curriculum evaluation of madrasah and pesantren in MAN 2 Pasuruan. This study uses a qualitative approach with case study type research at MAN 2 Pasuruan. The data collection is conducted with observation, interview, and documentation. Data analysis uses data reduction techniques, data presentation, drawing conclusion and verification. The results of the research in MAN 2 Pasuruan are: 1) integrative curriculum plannings of madrasah and pesantren are applied by: a) curriculum objectives integration and b) integration of organization of curriculum content. 2) Implementations of integrative curriculum madrasah and pesantren are done by: a) integration of program implementation of the curriculum and b) integration of curriculum implementation supervision. 3) Evaluation of integrative curriculum madrasah and pesantren is done by evaluate the curriculum in coordination between madrasah and pesantren, which include: a) evaluation of curriculum context, b) evaluation of curriculum input, c) evaluation of curriculum process and d) evaluation of the curriculum products.